Increased Risk of Postpartum Depression in Women With Allergic Rhinitis During Pregnancy: A Population-Based Case-Control Study. (October 2022) - Yang, Zhi-Chao; Wang, Li-Xin; Yu, Yang; Lin, Huan-Yu; Shih, Liang-Chun
Objectives: Allergic rhinitis (AR) is associated with increased risk of major depression in the general population, however, no previous study has evaluated its role among pregnant women. We aimed to investigate the potential impact of AR during pregnancy on the development of postpartum depression (PPD). Methods: This is a population-based case-control study. Data were retrieved from the National Health Insurance Research Database (NHIRD). Medical records of a total of 199 470 deliveries during 2000 and 2010 were identified. Among which, 1416 women with PPD within 12 months after delivery were classified as the case group, while 198 054 women without PPD after delivery formed the control group. Univariate and multivariate regression analyses were conducted to determine the associations between AR during pregnancies and other study variables with PPD. Results: AR during pregnancy was found in 9.53% women who developed PPD and 5.44% in women without PPD. After adjusting for age at delivery, income level, various pregnancy and delivery-related conditions, asthma, atopic dermatitis and other medical comorbidities in the multivariate analysis, AR was significantly associated with increased odds of PPD (aOR: 1.498, 95% CI: 1.222-1.836). Conclusion: AR during pregnancy was independently and significantly associated with an approximately 50% increased risk of PPD among women giving birth. Closely monitoring of AR is warranted in the future in order to optimize mother and child outcomes after delivery.